Performance Over Enjoyment? Effect of Game-Based Learning on Learning Outcome and Flow Experience - Chan, Kevin; Wan, Kelvin; King, Vivian (Frontiers in Education, 2021)
Competitiveness in serious games and game-based learning contexts, have been suggested to be associated with variations in flow experience pertaining from game experience. Evidence from the game-based learning literature suggested that game-based learning in general enhances learning outcomes, and applicable to learning psychology at the undergraduate level. Yet the magnitude of such effect remains mixed from empirical evidence. The current study examines whether game-based learning, in competitive and non-competitive game format, would lead to differentiated gains on learning outcomes, perceived flow experience from game-based learning, and their interaction. We wish to test whether competitive and non-competitive formats of game-based learning could be characterised with different configurations of game flow experience that encapsulate the game-based learning experience, as well as the extent to which such predominant game flow experience would correlate with observed learning outcomes from featured game-based learning conditions. Effect of game-based learning was tested with an 2X2 experimental design. Participating learners (n=142) were randomly assigned into either one out of four experimental conditions based on a 2X2 block design with two independent variables, competitiveness of game-based learning (competitive vs non-competitive), and format of game-based learning (group vs individual). Participating Learners in each of the conditions were assessed on learning outcomes related to the subject matters intended for the game-based learning artefacts. Results on learning outcomes revealed a significant main effect of competitiveness of game-based learning was observed, but not for format nor interaction effect. Main effect of format of game-based learning when learning in groups was observed from another two-way ANOVA analysis in a finite set of eGameFlow constructs including feedback, autonomy, goal clarity, and social interaction. Interaction effects between competitiveness of game-based learning and format was observed in autonomy and goal clarity constructs. Results from this study suggested that competitiveness and group format does not necessarily warrant improvement on learning outcomes in the game-based learning context. Main effects on cognitive flow dimensions align with the performance orientation among Asian learners. Further research would shed light on identifying levels of optimal gamified elements while assuring improvement on intended learning outcomes in the Asian tertiary education context.